Study on the Application of Li4Ti5O12 Battery on EMUs - 苏剑; 李红兵 (机车电传动)
Based on light-weight design demand analysis of EMUs assistant battery system,basic performance of present batteries were compared. With test of charge/discharge rate, high/low temperature performance and cycle life of Li4Ti5O12 battery, feasibility of Li4Ti5O12 battery using on EMUs light-weight design was analyzed, and settle scheme of batteries application was provided.